Research progress of two-pore potassium channel in myocardial ischemia-reperfusion injury - Zhang, Yue; Li, Jing; Pan, Jiamei; Deng, Shengli (Frontiers in Physiology, 2024)
Myocardial ischemia-reperfusion injury (MIRI) is a secondary injury caused by restoring blood flow after acute myocardial infarction, which may lead to serious arrhythmia and heart damage. In recent years, the role of potassium channels in MIRI has attracted much attention, especially the members of the two-pore domain potassium (K2P) channel family. K2P channel has unique structure and function, and the formation of its heterodimer increases its functional diversity. This paper reviews the structural characteristics, types, expression and physiological functions of K2P channel in the heart. In particular, we pay attention to whether members of the subfamily such as TWIK, TREK, TASK, TALK, THIK and TRESK participate in MIRI and their related mechanisms. Future research will help to reveal the molecular mechanism of K2P channel in MIRI and provide new strategies for the treatment of cardiovascular diseases.